NCAR/NSF C-130 Multichannel Cloud Radiometer [NCAR/EOL] (Arctic Data Center, 2016)
The MCR is a seven-channel radiometer that scans between *plusmn*45*deg* about the NSF/NCAR C-130 track. This dataset contains MCR data collected during the Surface Head Budget of the Arctic Ocean Project (SHEBA). This data can be viewed using MCRVIEW available for download below.